Evaluation of the Spatial Disparities in the Youth Suitability of Shenzhen Public Primary School Campuses - Yixuan Li; Chengyu Chen (Buildings, 2023)
This paper delves into the critical issue of youth suitability in the public primary school campuses in Shenzhen Central District, China. Youths constitute a crucial part of the urban population, contributing greatly to social wealth; thus, considering their needs and well-being is imperative in the urban planning and development process. The paper employs a comprehensive Python script tool, based on ArcGIS, that is augmented with an empirical investigation and data from the statistical yearbook in order to conduct a meticulous evaluation of the youth suitability of primary school campuses. The results of the study reveal spatial differences in the youth suitability of primary school campuses, with the suitability diminishing from the district’s inner areas to its outer regions. Additionally, the study unearths that primary school campuses in the Shenzhen Central District are generally stratified, and that the campus service space could be appropriately categorized into several groups based on the dual criteria of accessibility as well as youth suitability. Finally, this study provides illuminating decision-making suggestions for optimizing the youth suitability of primary school campuses in Shenzhen Central District, highlighting the crucial role of education policies, regional economic development, and campus infrastructure improvements in nurturing inclusive, vibrant, and sustainable urban environments.